Preparation method and application of nitrogen-doped porous carbon supported metal catalyst
By preparing nitrogen-doped porous carbon-supported single-atom metal catalyst, the problems of low specific surface area and unclear active center structure of the existing catalyst are solved, and efficient catalysis in the N-formylation reaction between amine and CO2 is achieved. Shows good recycling performance.
Patent Information
- Application Number
- CN202310951803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing porous polymer pyrolysis preparation porous carbon materials have shortcomings such as low specific surface area, uncontrollable coordination state of metal atoms, uncontrollable metal atom spacing, and unclear active center structure, which limits its practical application.
The quaternization reaction of tetra(4-pyridyl)porphyrin, tetra(4-pyridyl)porphyrin metal complex and polybrominated methylbenzene is carried out to prepare a metal-doped porous ionic polymer, and then adsorbs urea and pyrolytic , a nitrogen-doped porous carbon-supported single-atom metal catalyst was prepared.
The prepared catalyst has a high specific surface area, high nitrogen content, adjustable metal loading and metal atom spacing, and a clear active center structure, which significantly improves the catalytic activity in the N-formylation reaction between amine and CO2, and its activity is much higher than that of Ru/C, Ir/C and Pd/C catalysts were commercialized, and the catalysts remained well active after 20 recycles.
Smart Images

Figure CN119433582A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of a nitrogen-doped porous carbon-supported metal catalyst. Background Art
[0002] In recent years, with the burning of a large number of fossil fuels, global energy depletion and greenhouse effect problems have become increasingly serious, posing serious challenges to human survival and sustainable development. As the most important greenhouse gas, CO2 contributes up to 70% to the rise in global temperatures. On the other hand, CO2 is a carbon resource with abundant reserves and low cost. Based on this, converting greenhouse gas CO2 into fuel or chemicals and realizing CO2 resource utilization is an effective way to achieve a sustainable development strategy.
[0003] Formamide has a wide range of uses and plays an important role in drug synthesis. The N-formylation reaction of amines with CO2, using CO2 as a formylating agent, provides a green synthetic route for the formylation of amines. However, due to the thermodynamic and kinetic stability of CO2, the activity of the reaction is not high. Moreover, traditional homogeneous coordination compound catalysts have a series of problems such as difficult separation of products, high catalyst cost, easy deactivation of catalysts, and difficulty in recycling catalysts, which restrict the industrial application of the reaction. Therefore, the development of highly active heterogeneous catalysts to achieve efficient conversion and catalyst recycling in this reaction is of great significance for promoting the industrialization of this synthetic route.
[0004] Since it was proposed in 2011, single-atom catalysts have shown great application potential in the field of heterogeneous catalysis due to their nearly 100% atomic utilization and unique structural characteristics. In recent years, the preparation of porous carbon materials loaded with metal single-atom catalysts by pyrolysis of metal-doped porous polymers has attracted much attention due to its simple method and easy-to-control structure. However, the catalysts prepared by pyrolysis of porous polymers to prepare porous carbon materials loaded with metal single-atom catalysts still face the disadvantages of low specific surface area, uncontrollable metal atom coordination state, uncontrollable metal atom spacing, and unclear active center structure, which greatly restricts its practical application. For example, patent application CN113856722A uses melamine, terephthalaldehyde and dimethyl sulfoxide as raw materials to prepare nitrogen-rich porous polymers, which are further mixed with metal acetates and carbonized at 600-900 ° C to obtain metal single-atom catalysts. This method solves the problem of low efficiency in the preparation of single-atom catalysts. However, the single-atom catalysts prepared by this method have the disadvantages of uncontrollable metal atom coordination state, uncontrollable metal atom spacing, and unclear active center structure. Based on this, developing a controllable preparation method for metal single-atom materials with simple preparation, adjustable metal atomic spacing, and clear active center structure is of great practical significance for improving the catalytic activity of single-atom catalysts and realizing their industrial applications. Summary of the invention
[0005] In view of the deficiencies in the prior art, the inventors of the present application used tetra(4-pyridyl)porphyrin, tetra(4-pyridyl)porphyrin metal complexes, and polybrominated methylbenzenes to carry out quaternization reaction to prepare metal-doped porous ion polymers. Further, the porous ion polymers were pyrolyzed after adsorbing urea, and nitrogen-doped porous carbon-supported single-atom metal catalysts with high nitrogen atom content, large specific surface area, adjustable metal loading and metal atomic spacing, and clear active center structure were prepared. These characteristics make the prepared catalyst show excellent catalytic activity in the N-formylation reaction of amine and CO2 to prepare formamide, and the activity is much higher than commercial Ru / C, Ir / C and Pd / C catalysts. This work provides a kind of efficient heterogeneous catalyst for the N-formylation reaction of CO2, and provides an important reference for the development of new and efficient nitrogen-doped porous carbon-supported metal catalysts.
[0006] The purpose of the present invention is to provide a preparation method and application of a nitrogen-doped porous carbon-supported metal catalyst to address the problems that the catalyst activity of the N-formylation reaction of amines and CO2 is low and the catalyst is not easy to recycle.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a nitrogen-doped porous carbon-supported metal catalyst comprises the following steps:
[0009] (1) Preparation of porous ionic polymers
[0010] 5,10,15,20-tetra(4-pyridyl)porphyrin, 5,10,15,20-tetra(4-pyridyl)porphyrin M complex and polybrominated methylbenzene are dissolved in an organic solvent in a certain proportion, reacted at 80-120° C. for 10-24 hours under the protection of an inert gas, and the obtained product is filtered and vacuum dried to obtain a porous ionic polymer.
[0011] Wherein, M is a transition metal, and M is at least one selected from Ru, Ir and Pd.
[0012] Furthermore, the 5,10,15,20-tetrakis(4-pyridyl)porphyrin M complex is one of a 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) complex, a 5,10,15,20-tetrakis(4-pyridyl)porphyrin iridium (III) complex, and a 5,10,15,20-tetrakis(4-pyridyl)porphyrin palladium (II) complex, and is preferably a 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) complex.
[0013] Furthermore, the 5,10,15,20-tetra(4-pyridyl)porphyrin ruthenium (II) complex is a coordination complex of 5,10,15,20-tetra(4-pyridyl)porphyrin and ruthenium (II) acetate, ruthenium (II) chloride or ruthenium (II) nitrate.
[0014] Furthermore, the 5,10,15,20-tetrakis(4-pyridyl)porphyrin iridium(III) complex is a coordination complex of 5,10,15,20-tetrakis(4-pyridyl)porphyrin and iridium(III) acetate, iridium(III) chloride or iridium(III) nitrate.
[0015] Furthermore, the 5,10,15,20-tetra(4-pyridyl)porphyrin palladium (II) complex is a coordination complex of 5,10,15,20-tetra(4-pyridyl)porphyrin and palladium (II) acetate, palladium (II) chloride or palladium (II) nitrate.
[0016] Furthermore, the molar ratio of the 5,10,15,20-tetra(4-pyridyl)porphyrin to the 5,10,15,20-tetra(4-pyridyl)porphyrin M complex is 100:(20-1), preferably 100:(10-2), and more preferably 100:(8-3).
[0017] Furthermore, the polybrominated methylbenzene is one of 1,4-di(bromomethyl)benzene, 1,3,5-tri(bromomethyl)benzene, 1,2,4,5-tetra(bromomethyl)benzene and hexa(bromomethyl)benzene, preferably hexa(bromomethyl)benzene or 1,3,5-tri(bromomethyl)benzene, more preferably hexa(bromomethyl)benzene.
[0018] Furthermore, the molar amount of the bromomethyl functional group of the polybrominated methylbenzene is 4 times the total molar amount of 5,10,15,20-tetrakis(4-pyridyl)porphyrin and 5,10,15,20-tetrakis(4-pyridyl)porphyrin M complex.
[0019] Furthermore, the organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone, preferably N,N-dimethylformamide.
[0020] Furthermore, the inert gas is one or a mixture of nitrogen, argon and helium.
[0021] (2) Preparation of porous ionic polymer / urea solid mixture
[0022] A certain amount of urea is dissolved in water to form a saturated solution, and the porous ionic polymer prepared in step (1) is added to the saturated solution. The resulting mixed solution is stirred at room temperature for 2-10 hours and dried by rotary evaporation to obtain a porous ionic polymer / urea solid mixture.
[0023] Furthermore, the mass ratio of the porous ion polymer to urea is 1:(0.5-10), preferably 1:(0.5-2), more preferably 1:(1-2), and more preferably 1:2.
[0024] (3) Preparation of Nitrogen-doped Porous Carbon-supported Metal Catalysts by Pyrolysis
[0025] The porous ion polymer / urea solid mixture obtained in step (2) is subjected to a programmed temperature increase to 550-1000°C for pyrolysis under the protection of an inert gas. After pyrolysis for a certain period of time, it is cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst. The metal in the obtained nitrogen-doped porous carbon-supported metal catalyst is dispersed in a single atom, and one metal single atom is coordinated with four nitrogen atoms to form M-N4.
[0026] Furthermore, the programmed heating rate is 1-5°C / min, preferably 2.5°C / min.
[0027] Furthermore, the pyrolysis time is 1-8h, preferably 1-2h.
[0028] Furthermore, the pyrolysis temperature is 600-800°C.
[0029] The present invention also provides the use of the nitrogen-doped porous carbon-supported metal catalyst or the nitrogen-doped porous carbon-supported metal catalyst prepared by the above-mentioned preparation method in the N-formylation reaction of amines and CO2.
[0030] The specific operations are as follows:
[0031] Amine and nitrogen-doped porous carbon-supported metal catalyst were added to a high-pressure reactor, the reactor was sealed, the air in the reactor was replaced with CO2, 3MPa CO2 was filled in, and then 3MPa H2 was filled in, and then the reactor was heated to 140-160°C and reacted for 1-100 hours. After the reaction, the product was qualitatively and quantitatively analyzed by gas chromatography.
[0032] Furthermore, the amine is piperidine, morpholine, dimethylamine, diethylamine, or N-methylaniline, preferably piperidine, morpholine, or N-methylaniline.
[0033] Furthermore, according to the reaction requirements, the above catalytic reaction can add one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and 1,4-dioxane as a reaction solvent.
[0034] Preferably, the catalytic reaction conditions are: reaction temperature is 150° C., and reaction time is 24 hours.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] (1) The present invention develops a method for preparing a metal single-atom catalyst with a simple method, adjustable metal loading and metal atomic spacing, and a clear active center structure.
[0037] (2) The catalyst prepared by the present invention has a large specific surface area, a high nitrogen content, an adjustable average distance between two adjacent metal atoms, and an active center consisting of a single metal atom and four nitrogen atoms. These factors combined make the catalyst exhibit excellent catalytic activity and stability in the N-formylation reaction of amines and CO2, with a conversion frequency TOF as high as 210562 (mol CHO mol metal -1 h -1 ), and after 20 cycles, the catalytic activity (TOF and yield) did not decrease significantly, showing good application prospects.
[0038] (3) In the catalyst preparation process of the present invention, there is no need to add activating agents such as KOH, thus avoiding post-treatment steps such as acid washing, reducing the emission of three wastes in the catalyst preparation process, and being environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the XRD pattern of NC-Ru-1 prepared in Example 1.
[0040] Figure 2 This is the nitrogen adsorption-desorption isotherm diagram of NC-Ru-1 prepared in Example 1.
[0041] Figure 3 This is the TEM image of NC-Ru-1 prepared in Example 1.
[0042] Figure 4 This is the SEM image of NC-Ru-1 prepared in Example 1.
[0043] Figure 5 This is the HAADF-STEM image of NC-Ru-1 prepared in Example 1.
[0044] Figure 6 This is the synchrotron radiation fitting result of NC-Ru-1 prepared in Example 1. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, so as to further illustrate the technical content of the present invention.
[0046] Example 1: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-1)
[0047] Take 2.81g (4.54mmol, 618.69g / mol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol, 755.24g / mol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.03g (3.2mmol, 635.65g / mol) of hexa(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the reactor temperature to 100°C under nitrogen protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.01g of porous ionic polymer.
[0048] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0049] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-1.
[0050] Elemental analysis showed that the nitrogen content of NC-Ru-1 was 8.52 wt% and the ruthenium content was 0.97 wt%. Figure 1 This is the XRD pattern of NC-Ru-1 prepared in Example 1, which shows that the prepared NC-Ru-1 is in an amorphous state, and no diffraction peaks of ruthenium or ruthenium oxide are observed. Figure 2 The nitrogen adsorption-desorption isotherm of NC-Ru-1 prepared in Example 1. The specific surface area of NC-Ru-1 is 1455 m 2 / g, containing micropores and mesoporous structures. Figure 3 , Figure 4 TEM and SEM images of NC-Ru-1 prepared in Example 1, respectively. No metal nanoparticles were observed, indicating that ruthenium was dispersed very uniformly. Figure 5 The HAADF-STEM image of NC-Ru-1 prepared in Example 1 proves that ruthenium is distributed in a single atom and the average distance between two adjacent Ru atoms is 1.3 nm. Figure 6 This is the synchrotron radiation fitting result of NC-Ru-1. The test results (black squares) and fitting results (red circles) prove that the catalyst presents an atomically dispersed Ru-N4 structure.
[0051] Example 2: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-2)
[0052] Take 2.57g (4.15mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.43g (0.57mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 1.98g (3.1mmol) of hexa(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 4.98g of porous ionic polymer.
[0053] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0054] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-2.
[0055] Elemental analysis shows that the nitrogen content of NC-Ru-2 is 8.54wt% and the ruthenium content is 2.55wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Ru-2 is 1370m 2 / g. XRD, TEM, SEM analysis showed that the prepared NC-Ru-2 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 0.6nm. Synchrotron radiation fitting results proved that the NC-Ru-2 catalyst presented an atomically dispersed Ru-N4 structure.
[0056] Example 3: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-3)
[0057] Take 2.92g (4.72mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.08g (0.10mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.04g (3.2mmol) of hexa(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.05g of porous ionic polymer.
[0058] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0059] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-3.
[0060] Elemental analysis shows that the nitrogen content of NC-Ru-3 is 8.46wt%, and the ruthenium content is 0.41wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Ru-3 is 1592m 2 / g. XRD, TEM, SEM analysis showed that the prepared NC-Ru-3 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 2.0nm. Synchrotron radiation fitting results proved that the NC-Ru-3 catalyst presented an atomically dispersed Ru-N4 structure.
[0061] Example 4: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-4)
[0062] Take 2.81g (4.54mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.27g (6.4mmol, 356.87g / mol) of 1,3,5-tri(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.27g of porous ionic polymer.
[0063] 4.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 2 hours, and rotary evaporated to dryness to obtain 8.0 g of a porous ion polymer / urea solid mixture.
[0064] The obtained 8.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-4.
[0065] Elemental analysis shows that the nitrogen content of NC-Ru-4 is 8.42wt%, and the ruthenium content is 1.01wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Ru-4 is 871m 2 / g. XRD, TEM, SEM analysis showed that the prepared NC-Ru-4 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 1.0nm. Synchrotron radiation fitting results proved that the NC-Ru-4 catalyst presented an atomically dispersed Ru-N4 structure.
[0066] Example 5: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-5)
[0067] Take 2.81g (4.54mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.27g (6.4mmol) of 1,3,5-tri(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure-resistant reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.27g of porous ionic polymer.
[0068] 2.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 2 hours, and rotary evaporated to dryness to obtain 6.0 g of a porous ion polymer / urea solid mixture.
[0069] The obtained 6.0 g porous ion polymer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-5.
[0070] Elemental analysis shows that the nitrogen content of NC-Ru-5 is 8.44wt% and the ruthenium content is 1.02wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Ru-5 is 710m 2 / g. XRD, TEM, SEM analysis showed that the prepared NC-Ru-5 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 0.9nm. Synchrotron radiation fitting results proved that the NC-Ru-5 catalyst presented an atomically dispersed Ru-N4 structure.
[0071] Example 6: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-6)
[0072] Take 2.81g (4.54mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.28g (6.4mmol) of 1,3,5-tri(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.27g of porous ionic polymer.
[0073] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0074] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-6.
[0075] Elemental analysis shows that the nitrogen content of NC-Ru-6 is 8.23wt% and the ruthenium content is 0.90wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Ru-6 is 1472m 2 / g. XRD, TEM, and SEM analysis showed that the prepared NC-Ru-6 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 1.4nm. Synchrotron radiation fitting results proved that the NC-Ru-6 catalyst presented an atomically dispersed Ru-N4 structure.
[0076] Example 7: Nitrogen-doped porous carbon supported Ru catalyst (NC-Ru-7)
[0077] Take 2.81g (4.54mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin ruthenium (II) chloride, and 2.28g (6.4mmol) of 1,3,5-tri(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen protection, stir and react for 12 hours, and filter and vacuum dry the product to obtain 5.27g of porous ionic polymer.
[0078] 8.0 g of urea was dissolved in water to form a saturated solution, and the porous ionic polymer prepared in step 4.0 g was added to the saturated solution. The resulting mixed solution was stirred at room temperature for 5 hours and dried by rotary evaporation to obtain 12.0 g of a porous ionic polymer / urea solid mixture.
[0079] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 900° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ru-7.
[0080] Elemental analysis shows that the nitrogen content of NC-Ru-7 is 8.27wt%, and the ruthenium content is 0.91wt%. Nitrogen adsorption and desorption isotherm analysis shows that the specific surface area of NC-Ru-7 is 908m 2 / g. XRD, TEM, and SEM analysis showed that the prepared NC-Ru-7 was amorphous and no metal nanoparticles were observed. HAADF-STEM analysis showed that ruthenium was distributed in a single atom, and the average distance between two adjacent Ru atoms was 0.9nm. Synchrotron radiation fitting results proved that the NC-Ru-7 catalyst presented an atomically dispersed Ru-N4 structure.
[0081] Example 8: Nitrogen-doped porous carbon supported Pd catalyst (NC-Pd)
[0082] Take 2.81g (4.54mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.19g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin palladium (II) chloride, and 2.01g (3.2mmol) of hexa(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 24 hours, and filter and vacuum dry the product to obtain 5.02g of porous ionic polymer.
[0083] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0084] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Pd.
[0085] Elemental analysis shows that the nitrogen content of NC-Pd is 8.46wt% and the palladium content is 1.22wt%. Nitrogen adsorption-desorption isotherm analysis shows that the specific surface area of NC-Pd is 1542m 2 / g. XRD, TEM, SEM, and HAADF-STEM analysis showed that palladium was distributed in a single atom, and the average distance between two adjacent Pd atoms was 1.2nm. Synchrotron radiation fitting results proved that the NC-Pd catalyst presented an atomically dispersed Pd-N4 structure.
[0086] Example 9: Nitrogen-doped porous carbon supported Ir catalyst (NC-Ir)
[0087] Take 2.78g (4.49mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 0.22g (0.25mmol) of 5,10,15,20-tetrakis(4-pyridyl)porphyrin iridium trichloride, and 2.00g (3.1mmol) of hexa(bromomethyl)benzene, add 30ml of N,N-dimethylformamide, transfer the solution to a pressure reactor, raise the temperature of the reactor to 100°C under nitrogen gas protection, stir and react for 24 hours, and filter and vacuum dry the product to obtain 5.00g of porous ionic polymer.
[0088] 8.0 g of urea was dissolved in water to form a saturated solution, 4.0 g of the porous ion polymer prepared above was added to the saturated solution, the resulting mixed solution was stirred at room temperature for 5 hours, and rotary evaporated to dryness to obtain 12.0 g of a porous ion polymer / urea solid mixture.
[0089] The obtained 12.0 g porous ionomer / urea solid mixture was heated to 600° C. at a rate of 2.5° C. / min for pyrolysis for 2 h under nitrogen gas protection, and then naturally cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst, which was recorded as NC-Ir.
[0090] Elemental analysis shows that the nitrogen content of NC-Ir is 8.45wt%, and the iridium content is 2.37wt%. Nitrogen adsorption and desorption isotherm analysis shows that the specific surface area of NC-Ir is 1479m 2 / g. XRD, TEM, SEM, and HAADF-STEM analysis showed that iridium was distributed in a single atom, and the average distance between two adjacent Ir atoms was 1.3nm. Synchrotron radiation fitting results proved that the NC-Ir catalyst presented an atomically dispersed Ir-N4 structure.
[0091] Example 10: Catalytic N-formylation of piperidine with CO2
[0092] 85.1 g (1 mol) piperidine and 2.00 mg NC-Ru-1 catalyst (Ru = 19.4 μg) were added to the autoclave, the autoclave was sealed, the air in the autoclave was replaced with CO2, 3 MPa CO2 was filled, and then 3 MPa H2 was filled, and then the autoclave was heated to 150°C and reacted for 24 hours. After the reaction was completed, the product was qualitatively and quantitatively analyzed by gas chromatography. The yield of N-formylpiperidine was 97%, and the conversion frequency TOF was 210562 (mol CHO mol metal -1 h -1 ).
[0093] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ru-2 catalyst (Ru = 51 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 91%, and the TOF was 75141 (mol CHO mol metal -1 h -1 ).
[0094] 2.00 mg of NC-Ru-1 catalyst was replaced by 5.00 mg of NC-Ru-3 catalyst (Ru = 20.5 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 73%, and the TOF was 149961 (mol CHO mol metal -1 h -1 ).
[0095] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ru-4 catalyst (Ru = 20.2 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 64%, and the TOF was 133425 (mol CHO mol metal -1 h -1 ).
[0096] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ru-5 catalyst (Ru = 20.4 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 57%, and the TOF was 117667 (mol CHO mol metal -1 h -1 ).
[0097] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ru-6 catalyst (Ru = 18.0 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 81%, and the TOF was 189506 (mol CHO mol metal -1 h -1 ).
[0098] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ru-7 catalyst (Ru = 18.2 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 64%, and the TOF was 148087 (mol CHO mol metal -1 h -1 ).
[0099] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Pd catalyst (Pd = 24.4 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 12% and the TOF was 21824 (mol CHO mol metal -1 h -1 ).
[0100] 2.00 mg of NC-Ru-1 catalyst was replaced by 2.00 mg of NC-Ir catalyst (Ir = 47.4 μg), and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 37% and the TOF was 62512 (mol CHO mol metal -1 h -1 ).
[0101] 2.00 mg of NC-Ru-1 catalyst was replaced with 2.00 mg of commercial Ru / C catalyst (Ru content 5.0 wt%, Ru = 0.1 mg) from Dalian General Chemical Co., Ltd., and the other conditions and parameters remained unchanged. The yield of N-formylpiperidine was 0.2% and the TOF was 160 (mol CHO mol metal-1 h -1 ).
[0102] 2.00 mg of NC-Ru-1 catalyst was replaced with 2.00 mg of Shanghai Aladdin Ir / C catalyst (Ir content 5.0 wt%, Ir = 0.1 mg), and the other conditions and parameters remained unchanged, and almost no target product was detected.
[0103] 2.00 mg of NC-Ru-1 catalyst was replaced with 2.00 mg of Shanghai Anage Pd / C catalyst (Pd content 5.0 wt%, Pd = 0.1 mg), and the other conditions and parameters remained unchanged, and almost no target product was detected.
[0104] Example 11: NC-Ru-1 catalyzes N-formylation of morpholine with CO2
[0105] Referring to Example 10, 85.1 g (1 mol) of piperidine was replaced by 87.1 g (1 mol) of morpholine, and the other conditions and parameters remained unchanged. The yield of N-formylmorpholine was 94%, and the conversion frequency TOF was 204049 (mol CHO mol metal -1 h -1 ).
[0106] Example 12: N-Formylation Reaction of N-Methylaniline with CO2 Catalyzed by NC-Ru-1
[0107] Referring to Example 10, 85.1 g (1 mol) of piperidine was replaced by 107.15 g (1 mol) of N-methylaniline, and the other conditions and parameters remained unchanged. The yield of N-formyl-N-methylaniline was 76%, and the conversion frequency TOF was 164976 (mol CHO mol metal - 1 h -1 ).
[0108] Example 13: NC-Ru-1 catalyzes N-formylation of dimethylamine with CO2
[0109] Add 100 ml of dimethylamine solution in N-methylpyrrolidone (containing 14.7 g of dimethylamine) and 2.00 mg of NC-Ru-1 catalyst to the autoclave, seal the autoclave, replace the air in the autoclave with CO2, fill it with 3 MPa CO2, and then fill it with 3 MPa H2, then heat the autoclave to 150°C and react for 24 hours. After the reaction, use gas chromatography to conduct qualitative and quantitative analysis of the product. The yield of N,N-dimethylformamide is 77%, and the TOF is 54499 (mol CHO mol metal-1 h -1 ).
[0110] 14.7 g of dimethylamine was replaced by 23.84 g of diethylamine, and the other conditions and parameters remained unchanged. The yield of N,N-diethylformamide was 31%, and the conversion frequency TOF was 21941 (mol CHO mol metal -1 h-1 ).
[0111] Example 14: Recycling of Catalyst
[0112] 85.1g piperidine and 2.00mg NC-Ru-1 catalyst were added to the autoclave, the autoclave was sealed, the air in the autoclave was replaced with CO2, 3MPa CO2 was filled, and then 3MPa H2 was filled, and then the autoclave was heated to 150°C and reacted for 24 hours. After the reaction, the product was qualitatively and quantitatively analyzed by gas chromatography. The yield of N-formylpiperidine was 97%. After the reaction was completed, the catalyst was centrifuged out, vacuum dried at 60°C for 12 hours, and the above catalytic reaction was repeated. The catalyst was reused 19 times to investigate the recycling performance of the catalyst. The catalytic activity results are shown in Table 1 below:
[0113] Table 1
[0114]
Claims
1. A nitrogen-doped porous carbon-supported metal catalyst, characterized in that: Prepared by the following method: (1) Preparation of porous ionic polymers Dissolving 5,10,15,20-tetra(4-pyridyl)porphyrin, 5,10,15,20-tetra(4-pyridyl)porphyrin M complex and polybrominated methylbenzene in an organic solvent in a certain proportion, heating and polymerizing at 80-120° C. under the protection of an inert gas to form a porous ionic polymer; wherein M is a transition metal, and M is selected from at least one of Ru, Ir and Pd; (2) Preparation of porous ionic polymer / urea solid mixture After the porous ion polymer prepared in step (1) absorbs a certain amount of saturated urea solution, it is vacuum dried to obtain a porous ion polymer / urea solid mixture; (3) Preparation of Nitrogen-doped Porous Carbon-supported Metal Catalysts by Pyrolysis The porous ion polymer / urea solid mixture obtained in step (2) is heated to 550-1000° C. under the protection of an inert gas and pyrolyzed for a period of time, and then cooled to room temperature to obtain a nitrogen-doped porous carbon-supported metal catalyst.
2. The nitrogen-doped porous carbon-supported metal catalyst according to claim 1, characterized in that: In the step (1), the 5,10,15,20-tetra(4-pyridyl)porphyrin M complex is a coordination complex of 5,10,15,20-tetra(4-pyridyl)porphyrin and an acetate, metal chloride or metal nitrate of ruthenium (II), iridium (III) or palladium (II).
3. The nitrogen-doped porous carbon-supported metal catalyst according to claim 1, characterized in that: In the step (1), the molar ratio of 5,10,15,20-tetra(4-pyridyl)porphyrin to 5,10,15,20-tetra(4-pyridyl)porphyrin M complex is 100:(20-1), preferably 100:(10-2), more preferably 100:(8-3); The molar amount of the bromomethyl functional group of polybrominated methylbenzene is 4 times the total molar amount of 5,10,15,20-tetra(4-pyridyl)porphyrin and 5,10,15,20-tetra(4-pyridyl)porphyrin M complex.
4. The nitrogen-doped porous carbon-supported metal catalyst according to claim 3, characterized in that: In the step (2), the mass ratio of the porous ionic polymer to urea is 1:(0.5-10), preferably 1:(1-2).
5. The nitrogen-doped porous carbon-supported metal catalyst according to claim 4, characterized in that: In the step (1), the polybrominated methylbenzene is one of 1,4-di(bromomethyl)benzene, 1,3,5-tri(bromomethyl)benzene, 1,2,4,5-tetra(bromomethyl)benzene and hexa(bromomethyl)benzene.
6. The nitrogen-doped porous carbon-supported metal catalyst according to claim 1, characterized in that: In the step (3), the pyrolysis temperature is 600-800°C.
7. The nitrogen-doped porous carbon-supported metal catalyst according to claim 1, characterized in that: In the step (1), the organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
8. Use of the nitrogen-doped porous carbon-supported metal catalyst according to any one of claims 1 to 7 in the N-formylation reaction of amines with CO2.
9. The use according to claim 8, characterized in that: The operation is as follows: add amine and nitrogen-doped porous carbon-supported metal catalyst into a high-pressure reactor, seal the reactor, replace the air in the reactor with CO2, fill it with 3MPa CO2, then fill it with 3MPaH2, and then heat the reactor to 140-160°C and react for 1-100 hours.
10. The use according to claim 9, characterized in that: The amine is at least one of piperidine, morpholine, dimethylamine, diethylamine and N-methylaniline.
Citation Information
Patent Citations
High-load metal monatomic catalyst as well as preparation method and application thereof
CN113856722A
Cited By
Preparation method and application of polyion liquid / alumina aerogel composite material
CN121016844A